Leptin and Adiponectin Levels in Patients with Chronic Hepatitis C with Carbohydrate and Lipid Metabolism Disorders - T. V. Antonova; N. S. Zhevnerova; M. A. Romanova; A. N. Kholodnaya; D. A. Lioznov (Журнал инфектологии, 2014)
Aim: to analyze leptin and adiponectin serum levels in patients with chronic hepatitis C in comparison with metabolic syndrome components, biochemical features and stage of hepatitis.Materials and methods: In 93 patients with chronic HCV in age 20-55 with a few symptomatic HCV-infection and minimal liver fibrosis stage serum leptin and adiponectin was measured. Associations between leptin, adiponectin and metabolic abnormalities, biochemical features, and hepatic fibrosis were determined.Results: Abdominal obesity was revealed at 40% patients, overweight – at 41%, insulin resistance – at 36,6% cases. The leptin and adiponectin levels were within normal limits range at most patients. Patients with minimal liver fibrosis had higher index of leptin by comparison to patients with moderate and severe fibrosis (r= – 0,402, р= 0,018). In patients with HCV genotype 3a the adiponectin level was below, than in HCV genotype 1b. Patients with abdominal obesity and overweight had higher leptin and lower adiponectin indexes by comparison to patients without these metabolic abnormalities. Direct cross-correlation between the leptin level and body mass index (r=0,358, p=0,001), waist circumference (r=0,292, p=0,01); negative cross-correlation between the adiponectin level and body mass index (r=- 0,435, р <0,021), waist circumference (r=- 0,386, р =0,001) were displayed.Conclusion: Leptin and adiponectin blood levels in HCVpatientis associated with abdominal obesity and overweight. The connection of leptin level and liver fibrosis stage was revealed. Difference of adiponectin level in HCV-patients with 3a and 1b genotypes of virus was found.